Tools for Advanced Control Processes in Plastic Injection Moulding Technology - Cezova, Eliska (Manufacturing Technology Journal, 2023)
This paper describes some tools usable for quality control in plastic injection moulding. The introductory part presents tools for quality management, the use of which is demonstrated in the next part using a practical example. The selection of suitable methods was based on proven methods for quality management. They were selected to work in synergy. The author's contribution is the modification of the PDCAI method, which was enriched by another step, namely, innovation. The last part of the article presents is a demonstration of FMEA, Ishikawa diagram, and Pareto diagram.
Keywords: Quality control; Control processes; Injection moulding; Plastic technology; Pareto diagram; Ishikawa diagram; PDCAI; FMEA